2019
DOI: 10.1371/journal.pntd.0007313
|View full text |Cite
|
Sign up to set email alerts
|

Competence of non-human primates to transmit Leishmania infantum to the invertebrate vector Lutzomyia longipalpis

Abstract: Leishmaniasis is a zoonotic disease of worldwide relevance. Visceral leishmaniasis is endemic in Brazil, where it is caused by Leishmania infantum with Lutzomyia longipalpis being the most important invertebrate vector. Non-human primates are susceptible to L . infantum infection. However, little is known about the role of these species as reservoirs. The aim of this study was to evaluate the transmissibility potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Until now, the infectiousness of asymptomatic hosts has been studied almost exclusively in visceral leishmaniasis. Xenodiagnostic experiments showed the transmissibility of L. donovani from asymptomatic BALB/c mice [18] and L. infantum from different mammalian hosts [36][37][38][39][40][41]. The infectiousness of asymptomatic dogs infected with L. infantum has been studied most intensively, and meta-analysis of data published up to 2009 by Quinnell and Courtenay [13] showed that the proportion of infectious dogs increased significantly with clinical severity, but asymptomatic dogs were also infectious and infected a similar proportions of flies as sick dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, the infectiousness of asymptomatic hosts has been studied almost exclusively in visceral leishmaniasis. Xenodiagnostic experiments showed the transmissibility of L. donovani from asymptomatic BALB/c mice [18] and L. infantum from different mammalian hosts [36][37][38][39][40][41]. The infectiousness of asymptomatic dogs infected with L. infantum has been studied most intensively, and meta-analysis of data published up to 2009 by Quinnell and Courtenay [13] showed that the proportion of infectious dogs increased significantly with clinical severity, but asymptomatic dogs were also infectious and infected a similar proportions of flies as sick dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have concluded, for instance, that the circulating phlebotomine sand fly species are critical for the vectorial transmission of Leishmania spp. [95]; likewise, the mammals' role in parasite transmission concerns the vector, their meal preferences, and feeding behavior [96,97].…”
Section: Discussionmentioning
confidence: 99%
“…In wildlife there are serologic and molecular evidence of Leishmania infantum, Leishmania mexicana, Leishmania shawi, L. amazonensis, and Leishmania braziliensis in a wide range of NWP from endemic areas (4,23,28,78,89,90,112,120,154,172,182,212), but no symptomatic animals were identified. These findings could represent a public health concern once some species of NWP were competent in transmitting L. infantum to the invertebrate vector Lutzomyia longipalpis (150,182), being a potential reservoir of this parasite contributing to its maintenance in the environment. Trypanosoma cruzi is a mammal parasite, being the etiological agent of Chagas disease in humans, endemic throughout Latin America and classicaly transmitted by wound bites contaminated with feces of blood-sucking triatomine bugs (125).…”
Section: Leishmania Sppmentioning
confidence: 99%
“…Leishmaniosis, caused by Leishmania spp., has been reported in captive NWP from endemic regions with serology and molecular detection in asymptomatic animals, with few symptomatic cases, sometimes resulting in death (98,101,109,150,182). Pathological findings in a lethal case of a captive titi-monkey (Callicebus nigrifrons) infected by L. infantum were marked emaciation, severe pulmonary edema and hemorrhage, moderate splenomegaly, and lymphadenopathy, hepatic (109).…”
Section: Leishmania Sppmentioning
confidence: 99%